Abnormal functional connectivity of the habenula in mild cognitive impairment patients with depression symptoms revealed by resting‐state functional magnetic resonance imaging. (10th April 2023) - Cao, Yungang; Chen, Tao; Xia, Honglian; Zhu, Hong; Hou, Hongtao; Guo, Zhongwei; Wei, Fuquan; Liu, Xiaozheng
Abstract: Background: Recent research suggests that abnormalities in the habenula (HB), a core area of the brain that transmits reward information, may be a determinant of depression. However, it is not clear whether the functional connectivity (FC) pattern of the mild cognitive impairment (MCI) with and without depression symptoms is abnormal. Methods: In this study, we used resting‐state functional magnetic resonance imaging (fMRI) to examine the FC pattern of the HB in MCI patients with depression symptoms (D‐MCI). We acquired fMRI data from 54 subjects on a 3T MRI. Subjects collected included 16 patients with D‐MCI, 18 patients with MCI with no depression, and 20 healthy controls. One way ANCOVA and post hoc t ‐test were used to compare the difference in FC strength between the three groups. Results: The D‐MCI group had altered FC between the left HB and the right superior temporal gyrus, right inferior frontal gyrus/opercular part, and right middle frontal gyrus. The D‐MCI group had increased FC between the right HB and precuneus. Conclusions: These results suggest that the dysfunction of the HB–Default model network might be involved in the neural mechanism underlying depression in MCI. Key points: Recent research suggests that abnormalities in the habenula may be a determinant of depression. We used resting‐state functional magnetic resonance imaging to examine the functional connectivity (FC) pattern of the habenula in mild cognitive impairment (MCI) patients with depression symptoms. The MCI patients with depression symptoms had altered FC between the left habenula and the right superior temporal gyrus, right inferior frontal gyrus/opercular part, and right middle frontal gyrus. The MCI patients with depression symptoms group had increased FC between the right habenula and precuneus. The dysfunction of the habenula–Default model network might be involved in the neural mechanism underlying depression in MCI.